The Development of Open Banking and the Analysis of Third-Party Providers in Azerbaijan - Aliakbar Abbasov (Облік і фінанси)
The concept of open banking emerged less than 10 years ago, but today, millions of people in Europe use open banking products. In particular, in the UK, more than half of consumers have used them at least once. In Azerbaijan, the Central Bank took the first step towards implementing open banking in 2018, creating an instant payment system. In October 2021, the Central Bank of the Republic of Azerbaijan presented the Open Banking Roadmap for 2021-2025. This study reflects the current situation of introducing the open banking model in Azerbaijan. The primary research objective is to provide an overview of the open banking landscape in Azerbaijan, enhance information accessibility, and position it as a subject for comparative analysis with open banking practices adopted in various global regions. The author used qualitative methodology, including content analysis and comparison methods, to assess the readiness of the current financial sector for the open banking approach, its features, the development of third-party providers (TPPs), and the interest in the open banking approach. The official website of the Central Bank of the Republic of Azerbaijan and the results of previous independent research are the sources of data on open banking in Azerbaijan that were used for the analysis. The analysis revealed a limited development of TPPs offering open banking services and deficiencies related to the structural aspects of explicit consent in Azerbaijan. Although the implementation of open banking in Azerbaijan is somewhat later than in other countries, the steps taken by the government indicate a prospect for the rapid development of the open banking model. An important step in this direction was the adoption of the Law "On Payment Services and Payment Systems" covering open banking, the acquisition of licenses by TPPs within the framework of the regulatory approach, support of open banking services, and API support. Azerbaijan's current open banking development follows the regulatory-based European model and the Berlin Group standard for API security. It is considered more secure than other market-based and hybrid approaches in ensuring customer safety in open banking. For the faster development of the open banking model in Azerbaijan, features such as ease of use, speed of transactions, security, elimination of forced dependence on multiple banking applications using TPPs, and the ability to control personal financial data features should be presented to the society with social networks, and other by means.